PERAN PENANAMAN MODAL ASING DALAM PERTUMBUHAN EKONOMI NASIONAL MENURUT HUKUM INVESTASI - Siregar, Emiel Salim; Devi, Sri; Panjaitan, Togar Mariano; Siagian, Friska Febrianti br.; Nugraha, Ridho Andrean; Tanjung, Muhammad Haddad Alwi; Siregar, Bayu Adiva Yudhistira (Jurnal Ilmiah Wahana Pendidikan, 2024)
In practice, it is stated that the purpose of foreign investment in Indonesia can have a positive influence, in order to empower the community's economic improvement which will increase the circulation of money that can be maintained, and increase national economy growth. This study aims to analyze the regulation of Foreign Investment (PMA) in Indonesia based on Law No. 25 of 2007 concerning Investment, and the relation between PMA and national economic growth. The techniques used in writing this article are juridical-normative that moves towards law by approaching law. The results of the study concluded that foreign capital investors play a role in expanding the pace of public monetary development in Indonesia, but until now there are still difficulties in bureaucratic licensing management due to uncertainty in foreign investment regulations and also vulnerabilities between central and local government regulations. The consequences of providing legal guarantees for foreign investors in Indonesia are expected to be able to provide a large commitment or benefit to improve the national economy from the perspective of investment law regulation